Raça/Cor e rigidez arerial em crianças e adolescentes de uma população urbana brasileira - Zaniqueli, Divanei dos Anjos (2018)
Background: Increased stiffness of large arteries is an important determinant of cardiovascular disease risk. Higher values of arterial stiffness measured by carotid-femoral pulse wave velocity (cf-PWV) have been measured in adult African-Americans compared with whites. Studies assessing ethnic differences in cf-PWV among children and adolescents are scarce. This study sought to evaluate the association between race/color and arterial stiffness in Brazilian children and adolescents according to pubertal staging. Methods: Seven hundred and seventy-one children and adolescents (211 blacks and 560 nonblacks, 11.3 ± 2.7 years) were included. Arterial stiffness was evaluated by cf-PWV and central hemodynamic was assessed by radial applanation tonometry. The ethnic classification was obtained according to general phenotypes such as skin color, hair shape and facial traces. Pubertal staging was defining by using the Tanner scale. Results: Peripheral blood pressure was similar in black and nonblack across all pubertal stages, as well as central blood pressure, augmentation index heart rate corrected (Aix@75) and its determinants, time to inflection point (Tr) and ejection duration (ED). Differently, cf-PWV was higher in blacks than nonblack pubescents (5.9 ± 0.7 vs. 5.6 ± 0.8 m/s, P< 0.001) and postpubescents (6.1 ± 0.7 vs. 5.7 ± 0.7 m/s, P= 0.042), whereas no difference was detected between black and nonblack prepubescents, even adjusting for age, MAP, sex, height, BMI, and HR. Conclusion: Our study showed that higher cf-PWV values in blacks appear in adolescence and are independent of blood pressure values. Therefore, our data suggest adolescence as a key phase for the appearance of the vascular profile found in adult black individuals.